2009
DOI: 10.1503/cmaj.080869
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in critical care: risk factors, prevention and disclosure

Abstract: Key points• Medication reconciliation may improve patient safety in the intensive care unit, and an updated list of medications should be maintained, including long-standing medications, the reasons for starting new medications and their planned stop dates and the reasons for discontinuing or holding old medications.• Engaging pharmacists in inpatient rounds in the intensive care unit may decrease the risk of adverse drug events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
90
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(104 citation statements)
references
References 112 publications
1
90
2
5
Order By: Relevance
“…It is used twice as much as in other hospital units because of the nature of the care provided and critical patient profiles requiring complex, urgent interventions. (1) Incorrect use and absence of safety standards undermine the efficacy of drugs and may cause serious incidents for patients and health institutions. (2) Medication-related incidents are circumstances or events that may or may not cause unnecessary harm to the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used twice as much as in other hospital units because of the nature of the care provided and critical patient profiles requiring complex, urgent interventions. (1) Incorrect use and absence of safety standards undermine the efficacy of drugs and may cause serious incidents for patients and health institutions. (2) Medication-related incidents are circumstances or events that may or may not cause unnecessary harm to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…(7) In this sense, intensive care units are identified as high-risk scenarios for medication-related incidents, whether due to the instability of the clinical condition of the patients or to the variability of situations and time pressure to which health care professionals are subjected, particularly nursing staff. (1) Despite advances in studies about medication-related incidents, it remains difficult to measure their extent, characteristics and prevalence, hindering coping with and management of risks related to drug therapy in intensive care units. (7) Thus, this study aimed to estimate the prevalence of medication-related incidents identified in records of patients hospitalized in an intensive care unit in a teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Surveys of the occurrence of medication errors inanaesthetic practice in anumber of countries showsignificant variations. While only 30% of the members of the Canadian Society of Anaesthesiologists admitted experiencing errors in their lifetime career [13] , 89% anaesthesiologists in New Zealand admitted making an error in practice [14] and these figure still varies when compared with data from other advance countries.…”
Section: Introductionmentioning
confidence: 99%
“…3 Los pacientes que se encuentran en la Unidad de Cuidados Intensivos (UCI) experimentan 1,7 errores clínicos cada día y muchos de ellos se exponen a un error potencialmente fatal durante su estadía. 4 Los EPM son responsables del 78% de los errores graves en la UCI. 5 En los pacientes pediátricos i n t e r n a d o s e n l a U C I , l o s medicamentos deben calcularse sobre la base del peso, superficie corporal, dosis máximas y mínimas, ajuste según función renal y/o hepática, lo que los torna más susceptibles de errores en la medicación.…”
unclassified